Blood glucose self-monitoring in type 2 diabetes: a randomised controlled trial - AJ Farmer; AN Wade; DP French; J Simon; P Yudkin; A Gray; A Craven; L Goyder; RR Holman; D Mant; A-L Kinmonth; HAW Neil (Health Technology Assessment, 2009)
Objectives: To determine whether self-monitoring of blood glucose (SMBG), either alone or with additional instruction in incorporating the results into self-care, is more effective than usual care in improving glycaemic control in non-insulin-treated diabetes. Design: An open, parallel group randomised controlled trial. Setting: 24 general practices in Oxfordshire and 24 in South Yorkshire, UK. Participants: Patients with non-insulin-treated type 2 diabetes, aged ≥ 25 years and with glycosylated haemoglobin (HbA1c) ≥ 6.2%. Interventions: A total of 453 patients were individually randomised to one of: (1) standardised usual care with 3-monthly HbA1c (control, n = 152); (2) blood glucose self-testing with patient training focused on clinician interpretation of results in addition to usual care (less intensive self-monitoring, n = 150); (3) SMBG with additional training of patients in interpretation and application of the results to enhance motivation and maintain adherence to a healthy lifestyle (more intensive self-monitoring, n = 151). Main outcome measures: The primary outcome was HBA1c at 12 months, and an intention-to-treat analysis, including all patients, was undertaken. Blood pressure, lipids, episodes of hypoglycaemia and quality of life, measured with the EuroQol 5 dimensions (EQ-5D), were secondary measures. An economic analysis was also carried out, and questionnaires were used to measure well-being, beliefs about use of SMBG and self-reports of medication taking, dietary and physical activities, and health-care resource use. Results: The differences in 12-month HbA1c between the three groups (adjusted for baseline HbA1c) were not statistically significant (p = 0.12). The difference in unadjusted mean change in HbA1c from baseline to 12 months between the control and less intensive self-monitoring groups was −0.14% [95% confidence interval (CI) −0.35 to 0.07] and between the control and more intensive self-monitoring groups was −0.17% (95% CI −0.37 to 0.03). There was no evidence of a significantly different impact of self-monitoring on glycaemic control when comparing subgroups of patients defined by duration of diabetes, therapy, diabetes-related complications and EQ-5D score. The economic analysis suggested that SMBG resulted in extra health-care costs and was unlikely to be cost-effective if used routinely. There appeared to be an initial negative impact of SMBG on quality of life measured on the EQ-5D, and the potential additional lifetime gains in quality-adjusted life-years, resulting from the lower levels of risk factors achieved at the end of trial follow-up, were outweighed by these initial impacts for both SMBG groups compared with control. Some patients felt that SMBG was helpful, and there was evidence that those using more intensive self-monitoring perceived diabetes as having more serious consequences. Patients using SMBG were often not clear about the relationship between their behaviour and the test results. Conclusions: While the data do not exclude the possibility of a clinically important benefit for specific subgroups of patients in initiating good glycaemic control, SMBG by non-insulin-treated patients, with or without instruction in incorporating findings into self-care, did not lead to a significant improvement in glycaemic control compared with usual care monitored by HbA1c levels. There was no convincing evidence to support a recommendation for routine self-monitoring of all patients and no evidence of improved glycaemic control in predefined subgroups of patients. Trial registration: Current Controlled Trials ISRCTN47464659.